1984
DOI: 10.1073/pnas.81.9.2631
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight and structural nonequivalence of the mature alpha subunits of Torpedo californica acetylcholine receptor.

Abstract: A discrepancy of about 20% exists between the molecular weight of the a subunit of Torpedo californica electroplax acetylcholine receptor as determined by gel electrophoresis of the mature protein (Mr 40,000 ± 2000) and by nucleotide sequence analysis of cDNA (Mr z50,000 Each a subunit contains a high-affinity binding site for cholinergic ligands and possibly for a-bungarotoxin (1). These two sites are not equivalent. After reduction of a disulfide bridge close to the binding sites, they both can be covalentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

1985
1985
1990
1990

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 38 publications
1
20
0
1
Order By: Relevance
“…Our results agree with the findings of others who observe a 19-kDa MBTA-labeled fragment and a 17-kDa carbohydrate-containing fragment following digestion of the a subunit with V8 protease (15). It has been proposed by Conti-Tronconi et al (14) that the NH2 termini of both the 19-and 17-kDa fragments begin at AA 46 and that both fragments contain asparagine-141. Similarly, Lindstrom et al (16) propose that these two fragments begin at AA 42.…”
Section: Ser-----------------------------asn---asp---ser---cys-cys---supporting
confidence: 83%
See 1 more Smart Citation
“…Our results agree with the findings of others who observe a 19-kDa MBTA-labeled fragment and a 17-kDa carbohydrate-containing fragment following digestion of the a subunit with V8 protease (15). It has been proposed by Conti-Tronconi et al (14) that the NH2 termini of both the 19-and 17-kDa fragments begin at AA 46 and that both fragments contain asparagine-141. Similarly, Lindstrom et al (16) propose that these two fragments begin at AA 42.…”
Section: Ser-----------------------------asn---asp---ser---cys-cys---supporting
confidence: 83%
“…To use asparagine-141 as a reference point to map the BTX-binding site, it was necessary to demonstrate that all of the a subunit in the AcChoR possessed a marker for asparagine-141, namely an N-linked high-mannose oligosaccharide chain. This was especially important in light ofa recent report that the two a subunits in the AcChoR may differ in extent of glycosylation (14). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Conti-Tronconi et al also reported on another, larger fragment (19 kDa) that stains for carbohydrate only after prolonged staining with periodate/Schiff reagent and claimed that it is similar to their 17-kDa fragment in sequence, yet differs in the degree of glycosylation. If this were the case, then the 19-kDa fragment described by these authors (32) would not correspond to our 18-kDa fragment.…”
Section: Discussionmentioning
confidence: 97%
“…Extrasynaptic receptors display an antigenic site that synaptic receptors lack; it was suggested that this epitope might be a glyscosyl side chain on the receptor (Hall, Roisin, Gu & Gorin, 1983). Furthermore, the two a-subunits of the receptor seem to be differentially glyscosylated (Conti-Tronconi, Hunkapiller & Raftery, 1984). It is not yet known whether these differences in glycosyl side chains underlie the differential alkylation of the a-subunits by the tethered agonists and antagonists.…”
Section: Discussionmentioning
confidence: 99%